Analisis Sikap Peduli Lingkungan pada Peserta Didik di Sekolah Dasar - Siti Cholifah; Arya Setya Nugroho (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
The environment is now a topic that is always interesting to discuss in the world of education, especially at the elementary school. This research was motivated by some information that is often found, namely about the lack of caring attitudes towards the environment. For this reason, this attitude of caring for the environment must be implemented from an early age in accordance with government regulations. The purpose of this study was to discover how UPT SD Negeri 2 Gresik students feel about the environment. This type of research was descriptive qualitative with data collection techniques by means of documentation, observation, and interviews. This research was conducted at UPT SD Negeri 2 Gresik. Based on the results of the research, it can be seen that the environmental care attitude of UPT SD Negeri 2 Gresik students was in accordance with the five indicators of environmental care attitude, namely when there was trash scattered around, students immediately pick it up and throw it in the trash, save electricity usage when the KBM was over, always condition the class to keep clean, then carry out participatory-based environmental activities by cleaning trash cans, and finally participate in keeping the environmental clean.